2014
DOI: 10.1155/2014/626538
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Ability of the Stroke Survivor to Drive Their Own Recovery outside of Therapy during Inpatient Stroke Rehabilitation

Abstract: Aim. To explore factors affecting the ability of the stroke survivor to drive their own recovery outside of therapy during inpatient rehabilitation. Method. One-on-one, in-depth interviews with stroke survivors (n = 7) and their main carer (n = 6), along with two focus groups with clinical staff (n = 20). Data was thematically analysed according to group. Results. Stroke survivors perceived “dealing with loss,” whilst concurrently “building motivation and hope” for recovery affected their ability to drive thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 22 publications
(25 reference statements)
2
60
0
Order By: Relevance
“…Lifting of mood is consistent with findings that music has been shown to activate brain reward centers, including the ventral striatum . Stroke survivors, carers, and clinical staff have highlighted that time outside of therapy may be underexploited or wasted . Stroke survivors engaging in physical rehabilitation have also reported feeling bored and highly value engagement in physical activity .…”
Section: Discussionsupporting
confidence: 73%
“…Lifting of mood is consistent with findings that music has been shown to activate brain reward centers, including the ventral striatum . Stroke survivors, carers, and clinical staff have highlighted that time outside of therapy may be underexploited or wasted . Stroke survivors engaging in physical rehabilitation have also reported feeling bored and highly value engagement in physical activity .…”
Section: Discussionsupporting
confidence: 73%
“…Staff:patient ratio and mobilization policy might also influence activity levels. 11,12 There is evidence that environmental factors, like access to communal areas may help to increase activity levels in a rehabilitation setting. 13 Regardless of stroke unit model, it appears that patients spend most of their day alone.…”
mentioning
confidence: 99%
“…Carers of stroke survivors have highlighted the need for therapists to provide clear step‐by‐step instructions on how to complete practice outside of scheduled therapy (Eng et al ., ). In addition, carers have reported that insufficient time and too few training sessions are dedicated to carer training, such as how to use written and pictorial information and opportunities to demonstrate task performance to therapists (Bower, Gustafsson, Hoffman & Barker, ).…”
Section: Discussionmentioning
confidence: 97%
“…That finding is consistent with observational studies showing that stroke inpatients are more likely to practice when a therapist is present (Ada et al ., ; King et al ., ). Stroke survivors on rehabilitation units have described the time outside of therapy as ‘dead and wasted’ (Eng, Brauer, Kuys, Lord & Hayward, ), while carers suggest that this inactivity may be partly due to ‘not knowing what they could be doing themselves’ outside of structured therapy time (Eng et al .). Unsupervised practice activities identified in this review that can be taught to stroke inpatients include the GRASP protocol for upper limb practice (Harris et al ., ), and mental practice delivered using a tape recording (Page et al ., ).…”
Section: Discussionmentioning
confidence: 99%